RM50,000 Turning Point For Undergraduate - The Sun, (2008)
An undergraduate from Universiti Putra Malaysia last week went home RM50,000 richer after winning the finale of Turning Point - an online interative game hosted by AXA Affin Life Insurance Berhad.